Associations of region‐specific visceral adiposity with subclinical atrial dysfunction and outcomes of heart failure - Bo‐Han Huang; Shun‐Chuan Chang; Chun‐Ho Yun; Kuo‐Tzu Sung; Yau‐Huei Lai; Chi‐In Lo; Wen‐Hung Huang; Shih‐Chieh Chien; Lawrence Yu‐Min Liu; Ta‐Chuan Hung; Jen‐Yuan Kuo; Jiun‐Lu Lin; et al. (ESC Heart Failure, 2020)
Abstract Aims Excessive visceral adiposity (VAT) plays an essential role in metabolic derangements with those close to heart further mediates myocardial homeostasis. The disparate biological links between region‐specific VAT and cardiometabolic profiles as mediators influencing atrial kinetics remain unexplored. Methods and results Among 1326 asymptomatic individuals, region‐specific VAT including peri‐aortic root fat (PARF) and total pericardial fat (PCF) of cardiac region, together with thoracic peri‐aortic adipose tissue (TAT), was assessed using multiple‐detector computed tomography. VAT measures were related to functional left atrial (LA) metrics assessed by speckle‐tracking algorithm and clinical outcomes of atrial fibrillation (AF) and heart failure (HF). Multivariate linear regression models incorporating body fat, metabolic syndrome, and E/TDI‐e' consistently demonstrated independent associations of larger PARF/PCF with peak atrial longitudinal systolic strain (PALS) reduction, higher LA stiffness, and worsened strain rate components; instead, TAT was independently associated with cardiometabolic profiles. PARF rather than PCF or TAT conferred independent prognostic values for incident AF/HF by multivariate Cox regression (adjusted hazard ratio: 1.56, 95% confidence interval: 1.17–2.08, P = 0.002) during a median of 1790 days (interquartile range: 25th to 75th: 1440–1927 days) of follow‐up, with subjects categorized into worst PALS and largest VAT tertiles demonstrating highest events (all log‐rank P < 0.001). Mediation analysis showed that higher triglyceride and lower high‐density lipoproteins may serve as intermediary factors for effects between VAT and LA functional metrics, with lesser role by glucose level. Conclusions Visceral adiposity surrounding atrial region was tightly associated with subclinical atrial dysfunction and incident AF or HF beyond metabolic factors. Instead, peri‐aortic adiposity may mediate their toxic effects mainly through circulating cardiometabolic profiles.